Blood pressure measurement: Should technique define targets?. Issue 8 (16th July 2021) - Hiremath, Swapnil; Ramsay, Tim; Ruzicka, Marcel
Abstract: Accurate assessment of blood pressure (BP) is the cornerstone of hypertension management. The objectives of this study were to quantify the effect of medical personnel presence during BP measurement by automated oscillometric BP (AOBP) and to compare resting office BP by AOBP to daytime average BP by 24‐h ambulatory BP monitoring (ABPM). This study is a prospective randomized cross‐over trial, conducted in a referral population. Patients underwent measurements of casual and resting office BP by AOBP. Resting BP was measured as either unattended (patient alone in the room during resting and measurements) or as partially attended (nurse present in the room during measurements) immediately prior to and after 24‐h ABPM. The primary outcome was the effect of unattended 5‐min rest preceding AOBP assessment as the difference between casual and resting BP measured by the Omron HEM 907XL. Ninety patients consented and 78 completed the study. The mean difference between the casual and Omron unattended systolic BP was 7.0 mm Hg (95% confidence interval [CI] 4.5, 9.5). There was no significant difference between partially attended and unattended resting office systolic BP. Resting office BP (attended and partially attended) underestimated daytime systolic BP load from 24‐h ABPM. The presence or absence of medical personnel does not impact casual office BP which is higher than resting office AOBP. The requirement for unattended rest may be dropped if logistically challenging. Casual and resting office BP readings by AOBP do not capture the complexity of information provided by the 24‐h ABPM.